Coccolithophore culture collection and DNA/RNA isolation from samples and bioassays during UKOA cruise D366 around the British Isles. - Belestreri, Cecilia; Schroeder, Declan (British Oceanographic Data Centre, Natural Environment Research Council, 2014)
Water samples were collected by Cecilia Balestreri (Marine Biological Association) from CTD casts during cruise D366 on board RRS Discovery between 8th June and 6th July 2011. A total of 75 CTD casts were undertaken at stations in the NW European shelf sea, from which 18 were sampled for DNA and RNA extraction and culture collection and a further 5 were also used for Ocean Acidification bioassay experiments. The water was split into aliquots: one aliquot was used for in situ DNA extraction, while a second aliquot was filtered and the filters were preserved and maintained at -80 degree Celsius for RNA study. The DNA and RNA collected on board were used for genetic analysis. The environmental cultures collected during the cruise were subsequently used in the lab for Emiliania huxleyi isolation of clonal strains. The cruise was the first of three cruises which contributed to the NERC funded UK Ocean Acidification Research Programme.